High removal efficiency of tetracycline (TC) by biochar-supported zerovalent iron composite prepared by co-pyrolysis of hematite and pinewood. Issue 1 (1st January 2021) - Shi, Jun; Yang, Xianni; Zhang, Changai; Feng, Xue; Kong, Xiaofei; Wang, Xiaozhi; Wang, Shengsen
ABSTRACT: There is a need to prepare a high-efficient sorbent to remove the recalcitrant tetracycline (TC) in wastewater. Herein, biochar-supported zerovalent iron (BC/ZVI) was fabricated in nitrogen ambience via one-step co-pyrolysis of hematite and pinewood. X-ray diffractometer pattern indicated pinewood catalyzed conversion of hematite to ZVI, which was otherwise transformed to FeO, Fe3 O4 and ZVI without biomass. Batch sorption results indicated that TC removal capacities at pH 5 were 8.02, 177.70 and 301.39 mg g −1 by BC, ZVI and BC/ZVI, respectively. Overall, BC/ZVI showed excellent TC removal capacity through the complexation with Fe ions, surface adsorption and degradation. Thus, the agricultural and industrial wastes were converted via a one-step co-pyrolysis to a value-added product for highly efficient removal of TC in wastewater.